2011
DOI: 10.1007/s00429-011-0313-1
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of NPR-B immunoreactivity in the brainstem of Macaca fascicularis

Abstract: C-type natriuretic peptide (CNP), the most abundant natriuretic peptide hormone in the brain, plays an important role in neuroendocrine function. The physiological effects of CNP are mediated by the natriuretic peptide receptor-B (NPR-B). Although CNP and NPR-B have been detected in several brain regions, little is known about the neuroanatomical localization of NPR-B protein in the brainstem. In the present study, we investigated the topographical distribution of NPR-B immunoreactivity in the monkey brainstem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…While all NPRs have been identified in brainstem trigeminal nuclei [3234], little is known about the possible role of the natriuretic peptide system at TG level where nociceptive signals are transduced [3537]. A recent clinical report has shown that BNP levels are raised in the jugular vein blood during a migraine attack [38].…”
Section: Introductionmentioning
confidence: 99%
“…While all NPRs have been identified in brainstem trigeminal nuclei [3234], little is known about the possible role of the natriuretic peptide system at TG level where nociceptive signals are transduced [3537]. A recent clinical report has shown that BNP levels are raised in the jugular vein blood during a migraine attack [38].…”
Section: Introductionmentioning
confidence: 99%
“…Proteins were detected by using antibodies against NPR-C (Abcam) [15], p53 (Santa Cruz Biotechnology), Oct4 (sc-5279; Santa Cruz Biotechnology), Nanog (Bethyl Laboratories), NPR-A (Santa Cruz Biotechnology), NPR-B (Santa Cruz Biotechnology) [16], BNP (Chemicon), and b-actin (sc-47778; Santa Cruz Biotechnology). The secondary antibodies were peroxidase-conjugated IgG ( Jackson ImmunoResearch Lab, Inc.).…”
Section: Western Blottingmentioning
confidence: 99%
“…Therefore, to explore the relationship between NPR-C and p53, we treated ES cells with mitomycin C (MMC), an activator of the DNA damage p53/apoptosis pathway [22]. ES cells cultured in serum-free medium were treated for 6 h with MMC (5 mg/mL) alone or with MMC and cANF (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) (an NPR-C-specific agonist) together, and then we examined the expression of p53. As expected, MMC-treated cells showed a significant increase in the level of p53 protein.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies showed that BNP plays an essential role in cardiovascular homeostasis (Woodard and Rosado, 2007; Potter et al, 2009). However, other reports demonstrated that BNP and its receptors are expressed in several cell types that are not related to cardiovascular control, indicating BNP involvement in several functions (Cameron et al, 1996; Suda et al, 1998; Abdelalim et al, 2007, 2008a,b, 2013; Cao and Yang, 2008; Abdelalim and Tooyama, 2009, 2011a,b). …”
Section: Introductionmentioning
confidence: 99%